Iodine migration and its effect on hysteresis in perovskite solar cells - Li, Cheng; Tscheuschner, Steffen; Paulus, Fabian; Hopkinson, Paul E.; Kießling, Johannes; Köhler, Anna; Vaynzof, Yana; Hüttner, Sven (Advanced materials, 2016)
The migration and accumulation of iodide ions create a modulation of the respective interfacial barriers causing the hysteresis in solar cells based on methylammonium lead iodide perovskites. Iodide ions are identified as the migrating species by measuring temperature dependent current-transients and photoelectron spectroscopy. The involved changes in the built-in potential due to ion migration are directly measured by electroabsorption spectroscopy.